Chemotherapy-Induced Tumor Cell Death at the Crossroads Between Immunogenicity and Immunotolerance: Focus on Acute Myeloid Leukemia - Ocadlikova, Darina; Lecciso, Mariangela; Isidori, Alessandro; Loscocco, Federica; Visani, Giuseppe; Amadori, Sergio; Cavo, Michele; Curti, Antonio (Frontiers in Oncology, 2019)
In solid tumors and hematological malignancies, including acute myeloid leukemia, some chemotherapeutic agents, such as anthracyclines, have proven to activate an immune response via dendritic cell-based cross-priming of anti-tumor T lymphocytes. This process, known as immunogenic cell death, is characterized by a variety of tumor cell modifications, i.e. cell surface translocation of calreticulin, extracellular release of adenosine triphosphate and pro-inflammatory factors, such as high mobility group box 1 protein. However, alongside with immunogenic cell death, chemotherapy is known to induce inflammatory modifications within the tumor microenvironment, which may also elicit immunosuppressive pathways. In particular, DCs may be driven to acquire tolerogenic features, such as the overexpression of indoleamine 2,3-dioxygensase 1, which may ultimately hamper anti-tumor T-cells via the induction of T regulatory cells. The aim of this review is to summarize the current knowledge about the mechanisms and effects by which chemotherapy results in both activation and suppression of anti-tumor immune response. Indeed, a better understanding of the whole process underlying chemotherapy-induced alterations of the immunological tumor microenvironment has important clinical implications to fully exploit the immunogenic potential of anti-leukemia agents and tune their application.